The transmembrane protein of the human endogenous retrovirus--K (HERV-K) modulates cytokine release and gene expression. - Vladimir A Morozov (Public Library of Science (PLoS), 2013)
Numerous copies of endogenous retroviruses are present in the genome of mammals including man. Although most of them are defective, some, e.g., the human endogenous retroviruses HERV-K, were found to be expressed under certain physiological conditions. For instance, HERV-K is expressed in germ cell tumours and melanomas as well as in the placenta. Most exogenous retroviruses including the human immunodeficiency virus HIV-1 induce severe immunodeficiencies and there is increasing evidence that the transmembrane envelope (TM) proteins of these retroviruses may be involved. We show here that HERV-K particles released from a human teratocarcinoma cell line, a recombinant TM protein and a peptide corresponding to a highly conserved so-called immunosuppressive domain in the TM protein of HERV-K inhibit the proliferation of human immune cells, induce modulation of the expression of numerous cytokines, and modulate the expression of cellular genes as detected by a microarray analysis. The changes in cytokine release and gene expression induced by the TM protein of HERV-K are similar to those found previously induced by the TM protein of HIV-1. These data suggest that the mechanism of immunosuppression may be similar for different retroviruses and that the expression of the TM protein in tumours and in the placenta may suppress immune responses and thus prevent rejection of the tumour and the embryo.